Contagion of Fear - Kris James Mitchener; Gary Richardson (Center for Economic Studies and ifo Institute (CESifo), 2020)
The Great Depression is infamous for banking panics, which were a symptomatic of a phenomenon that scholars have labeled a contagion of fear. Using geocoded, microdata on bank distress, we develop metrics that illuminate the incidence of these events and how banks that remained in operation after panics responded. We show that between 1929-32 banking panics reduced lending by 13%, relative to its 1929 value, and the money multiplier and money supply by 36%. The banking panics, in other words, caused about 41% of the decline in bank lending and about nine-tenths of the decline in the money multiplier during the Great Depression.
Keywords: E44; G01; G21; L14; N22; 330; banking panics; Great Depression; contagion; monetary deflation